Synthesis of unsymmetrical benzil licoagrodione - Rattana Worayuthakarn (2018)
(Chemical Equation Presented) A synthesis of unsymmetrical 1,2-diarylethane-1,2-dione is reported involving the intramolecular cyclization of anionic benzylic ester of the aryl benzyl ether followed by oxidation employing dioxirane. With the use of microwave irradiation, licoagrodione was prepared from Claisen rearrangement of the corresponding allyl phenyl ether 1,2-diketone readily available from the Lindlar's reduction of the corresponding alkyne derivative. Subsequent removal of protecting groups then furnished the desired product. © 2008 American Chemical Society.